Visual Snow-Like Symptoms and Posterior Uveitis following COVID-19 Infection - Kathryn Kelani Braceros; Masumi G. Asahi; Ron P. Gallemore (Case Reports in Ophthalmological Medicine, 2021)
Visual snow (VS) is a neurologic condition consisting of a constant positive visual disturbance described as “static” with diagnosis requiring exclusion of competing neurologic and ophthalmologic disorders. The authors describe the first case of visual snow-like symptoms in a patient following coronavirus disease 2019 (COVID-19) infection. He was found to have a transient subtle mild inflammatory reaction in the vitreous and optic nerve edema which resolved, but the VS persisted. Our findings suggest that COVID-19 may precipitate a transient autoimmune response in some patients with resultant ocular inflammation as well as long-term symptoms of VS. This has potential implications for the understanding and treatment of complications related to COVID-19 and in VS.